Buildings for extreme environments. - McKeag, Sean (CIBSE, 2014)
Annotation This document on arid zones is the first of a three-part series that will reflect different climate zones; the others representing polar and tropical climates. With an ever-increasing number of our members working on international projects, or being based in locations unfamiliar to them, these documents have been designed to provide an introduction to topics that might be unfamiliar and to provide information upon which reasoned judgements may be made or lead to further research to be undertaken in support of their professional duties. We were fortunate in assembling an international steering group whose members were all experts in their respective fields.
Keywords: Buildings -- Environmental engineering -- Handbooks, manuals, etc.; Architecture and climate -- Handbooks, manuals, etc.; elektronické knihy; electronic books